Antibiotic Sensitivity Profile of Pasteurella multocida in Cattle in Malang, Indonesia - Dodik Prasetyo; Amri, Indah Amalia; Dian Siswanto; Rahayu Shafa Camila Sanjoyo; Monica Widyaningrum; Tanti Widya; Fidi Nur Eka Puji Dameanti (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
This study was conducted in Malang, Indonesia, to assess the prevalence and antibiotic susceptibility of Pasteurella multocida in cattle exhibiting clinical signs of respiratory disease. Nasal and tracheal swabs were collected from 50 cattle across multiple farms and tested for P. multocida. The isolates were identified through colony morphology, Gram staining, and biochemical tests, with 4 out of 50 samples (8%) testing positive for P. multocida. Antibiotic susceptibility was determined using the disk diffusion method, involving seven antibiotics commonly used in veterinary practice. Results showed that 75% of the isolates were sensitive to ceftriaxone, while amoxicillin-clavulanic acid was effective in 50% of cases. However, all isolates demonstrated resistance to erythromycin and tetracycline. These findings emphasize the importance of susceptibility testing to guide appropriate antibiotic therapy and prevent the development of resistance. Further research is necessary to monitor resistance patterns and improve treatment strategies for pasteurellosis in cattle.